Dunces, gourmands & petticoats - Room, Adrian (Lincolnwood, Ill. : NTC Publishing, 1997)
Contains more than 1,300 alphabetically arranged entries that explain how the meanings of modern English words have changed throughout history.
"Originally published as NTC's dictionary of changes in meaning"--T.p. verso.
Includes bibliographical references (p. 291-292).
Young Adult
Keywords: English language -- Etymology -- Dictionaries; English language -- Etymology -- Dictionaries